Customary Law and Cultural Identity of South Kalimantan: Challenges and Opportunities in the Modern Era - Khairunnisa, Khairunnisa; Muslim, Abdul Aziz; Rahmiati; Perdana, Gusti Muhammad Raja Putra (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Customary law (hukum adat) constitutes an integral component of the cultural identity of South Kalimantan, particularly among Banjar communities and other local groups. As a living legal system transmitted across generations, customary law not only regulates social relations but also preserves collective values, norms, and local wisdom. This study examines the role of customary law in maintaining cultural identity in South Kalimantan while analyzing the challenges and opportunities it faces in the modern era. Using a normative-empirical legal approach, the research combines doctrinal analysis of relevant legislation with field-based observations and secondary data to explore how customary norms interact with state law, modernization, and globalization. The findings indicate that customary law continues to play a significant role in strengthening social cohesion, conflict resolution, and the preservation of cultural values such as deliberation, mutual cooperation, and harmony with nature. However, it also encounters challenges, including legal marginalization, declining intergenerational transmission, and pressures from economic development and formal legal systems. Despite these challenges, modernization offers opportunities for the revitalization of customary law through legal recognition, institutional integration, and community-based cultural education. The study concludes that strengthening the synergy between customary law and state law is essential to ensure the sustainability of cultural identity in South Kalimantan in the context of contemporary societal change.